The Effect of Students’ Spiritual Intelligence on Science Process Skills in Kingdom Plantae Topic - Mukaromah, Nila Lailatul; Muhamad Jalil (Indonesian Journal of Mathematics and Natural Science Education, 2023)
This research is motivated by the word of Allah QS. Yusuf verse 105 and QS. Ar-rum verse 7, where there are various signs of Allah's greatness in the form of natural phenomena, but at this time many Muslims are negligent about this, while westerners are enthusiastic about natural phenomena that occur, but because they are not matched by spiritual intelligence led to scientific prostitution. Therefore, science process skills and spiritual intelligence are the main capital in understanding and discovering concepts related to natural phenomena, with the hope that from these phenomena we can develop science so that they become a source of help and help humans in understanding science. The purpose of this study was to determine the level of spiritual intelligence and Biology process skills of students of MA Nahdlatul Muslimin, and to determine the effect of spiritual intelligence on Biology process skills. This study uses a quantitative approach using simple linear regression analysis. The data collection technique uses a questionnaire instrument to measure spiritual intelligence and a performance instrument to measure biological process skills. The results of this study indicate the level of spiritual intelligence of students in the good category with an average percentage of 73.86%, and the level of Biological process skills in the good category with an average value of 78.68, and the influence of spiritual intelligence on Biological process skills is 13. 2%. Keywords: Intelligence, Process Skills, Spiritual,